Corrosion fatigue crack growth of serviced API 5L X56 submarine pipeline. (15th July 2022) - Guo, Yongjian; Shao, Yongbo; Gao, Xudong; Li, Tao; Zhong, Ying; Luo, Xiafei
Abstract: Corrosion fatigue tests on standard compact tensile (CT) specimens extracted from API 5L X56 pipe-in-pipe pipeline after servicing for 15 years have been conducted in air and in seawater environment (corrosion fatigue) respectively. Effects of maximum load, stress ratio and loading frequency on the fatigue crack growth (FCG) rate are considered in the fatigue tests, and such effects were investigated and discussed based on the tested results. The maximum load has a remarkable influence on the fatigue life of CT specimens. However, it has a slight effect on the two constants in Paris' law. Stress ratio has a significant influence on the FCG in middle stage, and FCG rate decreases with the stress ratio increases. With the increase of loading frequency, FCG rates decrease and fatigue life increase. Using scanning electron microscope, the fracture surface of the fatigue crack is observed and analyzed, and transgranular cleavage fracture is found on the fracture surface. The effects of the maximum load, the stress ratio and the loading frequency on the crystal surface and on the FCG mode were analyzed and compared based on such observation on the fracture surface of the fatigue crack. Highlights: Corrosion fatigue tests on CT specimens of serviced API 5L X56 submarine pipeline were conducted. Effects of maximum load, stress ratio and loading frequency on corrosion fatigue tests were investigated. Fatigue failure mechanism was analyzed based on scanning for fracture surface of fatigue crack. Effects of maximum load, loading frequency and stress ratio on fatigue life and FCG rates were introduced.